The rouble crisis and Russian wheat export controls - Linde Götz; Ulrich Koester; Thomas Glauben; Rudolf Bulavin (Intereconomics, 2015)
The Russian government implemented a wheat export tax in February 2015 to reduce food inflationary pressures resulting from the rouble's dramatic devaluation. This article discusses the causes of the rouble's instability and volatility, and the effects of the export controls on domestic wheat and bread prices. Although such export taxes are appealing to governments due to their low financial costs, we show that their economic costs are substantial in the long run. We suggest desisting from such trade-oriented measures and instead helping consumers adapt to high food prices.
Keywords: 330; Rubel; Volatilität; Abwertung; Exportsteuer; Weizen; Brot; Weizenpreis; Russland